2022
DOI: 10.1097/acm.0000000000004777
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Match Space: How Medical School and Specialty Characteristics Affect Residency Match Geography in the United States

Abstract: PurposeTo explore how school and specialty characteristics impact the geographic match location of U.S. senior medical students. MethodThe authors collected student match data between 2018 and 2020 from U.S. MD-granting medical schools and calculated the distance between students' medical schools and residency training programs. They use the term "match space" to describe this distance. Match space was codified on a 5-point ordinal scale by where the student matched: 1 = home institution, 2 = home state, 3 = a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This may be because of different and perhaps better resources and resource availability at these top-40 schools but also may be related to unconscious biases in the selection process. 16 Similarly, only 3% of reapplicants and 7% of unmatched first-time applicants were members of the AOA compared with successful first-time applicants (18%; P , 0.001; Table 3). Multiple studies have shown the positive relationship that the AOA status has on matching in orthopaedic surgery, and this difference is clearly visible within our subgroup analysis.…”
Section: Environmental Variablesmentioning
confidence: 94%
“…This may be because of different and perhaps better resources and resource availability at these top-40 schools but also may be related to unconscious biases in the selection process. 16 Similarly, only 3% of reapplicants and 7% of unmatched first-time applicants were members of the AOA compared with successful first-time applicants (18%; P , 0.001; Table 3). Multiple studies have shown the positive relationship that the AOA status has on matching in orthopaedic surgery, and this difference is clearly visible within our subgroup analysis.…”
Section: Environmental Variablesmentioning
confidence: 94%
“…These changes reflect the growing recognition of the importance of geography as a factor in the residency match process [9,10]. We have previously shown that school and specialty characteristics impact geography; however, little is known about how adaptations to the COVID-19 pandemic have influenced residency match geography across all specialties [11]. As we conducted this study, Cotner et.…”
Section: Introductionmentioning
confidence: 93%
“…We include the post-COVID-19 matched data to our prior publication with pre-COVID-19 matched data [11]; see the conceptual framework in Figure 1.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true in primary care institutions, which have less experience advising applications into competitive surgical specialties such as plastic surgery. 2 As such, medical students are largely responsible for educating themselves on their options should they have an interest in pursuing a residency program in plastic surgery.…”
Section: Introductionmentioning
confidence: 99%